2013
DOI: 10.2136/sh12-10-0028
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Evaluation of Soil Ecosystem Services

Abstract: Soil ecosystem services are diverse, valuable, and underappreciated. They are classified as provisioning, regulating, supporting, and cultural services. This paper is the product of a Soil Science Society of America task force convened to define and value ecosystem services derived from soil for the benefit of scientists, elected officials, and practitioners with the hope that a better understanding of soil ecosystem services will result in informed decisions in the use of soils. Soil provides medicines, build… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 76 publications
0
27
1
2
Order By: Relevance
“…However, experience has shown that translating lists of soil services into a picture that resonates with the public presents daunting challenges. Simply enumerating the many services provided directly or indirectly by soils to human populations, as some articles have done Comerford et al, 2013), has a tendency to become rapidly dreary and indigestible even for specialists. Fortunately, there are alternatives.…”
Section: Descriptions Of Soil Functions and Services Can Foster Commumentioning
confidence: 99%
See 1 more Smart Citation
“…However, experience has shown that translating lists of soil services into a picture that resonates with the public presents daunting challenges. Simply enumerating the many services provided directly or indirectly by soils to human populations, as some articles have done Comerford et al, 2013), has a tendency to become rapidly dreary and indigestible even for specialists. Fortunately, there are alternatives.…”
Section: Descriptions Of Soil Functions and Services Can Foster Commumentioning
confidence: 99%
“…Individuals who have a stake in the management of soils within a given geographical area can be asked to quantify each entry in a value-vs.-soil function matrix. Methods need to be elaborated for this type of valuation, in particular to avoid elements of this matrix being overly affected by interconnections among functions/services, which at the moment are challenging to disentangle (Comerford et al, 2013). Nevertheless, Breure et al (2012) and Rutgers et al (2012) have carried out such a multi-stakeholder, multifunctional valuation of soil services at different spatial and temporal scales.…”
Section: Valuation Of Ecosystem Services: Total Economic Valuementioning
confidence: 99%
“…The soil microbial community is a vital component of the soil biological system. It plays important roles in the nutrient cycles and energy flows, providing essential services to the forest ecosystem [1][2][3][4]. Bacteria and fungi are present in high proportions in soil microbial communities [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although these soil properties are extensively described and quantified in the existing soil databases they are often linked to the "mineral" commodities instead of "soil" stocks. For example, Comerford et al (2013) list numerous uses of soil materials/particles derived from "shallow to deep subsoils" (Table 3), but most likely these materials/particles are mined from mineral deposits (e.g., sand and gravel deposits are found on beaches, rivers, and streams). These "mineral" commodities are often monitored and valued on a regular basis in contrast to the "soil" commodities.…”
Section: Coarse Fragments and Rock Modifiersmentioning
confidence: 99%
“…Examples of "mineral" derived commodities in relation to sand, clay, and gravel (adapted fromComerford et al, 2013).…”
mentioning
confidence: 99%